2004
DOI: 10.1523/jneurosci.4651-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Early Serotonergic Projections to Cajal-Retzius Cells: Relevance for Cortical Development

Abstract: Although the serotonergic system plays an important role in various neurological disorders, the role of early serotonergic projections to the developing cerebral cortex is not well understood. Because serotonergic fibers enter the marginal zone (MZ) before birth, it has been suggested that they may influence cortical development through synaptic contacts with Cajal-Retzius (CR) cells. We used immunohistochemistry combined with confocal and electron microscopy to show that the earliest serotonergic projections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
123
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 82 publications
5
123
0
2
Order By: Relevance
“…For example, the reeler mouse, an autosomal recessive mutant in which reelin is defective, displays abnormalities in presubicular columns, which led Nishikawa et al (16) to postulate that reelin may act as a stop signal for dendritic extensions of cortical neurons. In addition, Janusonis et al (17) showed that serotonergic input on Cajal-Retzius cells is important for proper corticogenesis, as disruption of the serotonergic system during embryonic development results in lower levels of whole-brain reelin and a disturbed formation of cortical columns in the presubicular cortex. However, it is not clear whether the manifestations of these postnatal abnormalities are a mere consequence of the absence of reelin during the embryonic stage, or whether a different postnatal mechanism is responsible for the changes in cortical column formation.…”
Section: -Ht3 Receptor ͉ Cajal-retzius Cells ͉ Postnatal Developmentmentioning
confidence: 99%
“…For example, the reeler mouse, an autosomal recessive mutant in which reelin is defective, displays abnormalities in presubicular columns, which led Nishikawa et al (16) to postulate that reelin may act as a stop signal for dendritic extensions of cortical neurons. In addition, Janusonis et al (17) showed that serotonergic input on Cajal-Retzius cells is important for proper corticogenesis, as disruption of the serotonergic system during embryonic development results in lower levels of whole-brain reelin and a disturbed formation of cortical columns in the presubicular cortex. However, it is not clear whether the manifestations of these postnatal abnormalities are a mere consequence of the absence of reelin during the embryonic stage, or whether a different postnatal mechanism is responsible for the changes in cortical column formation.…”
Section: -Ht3 Receptor ͉ Cajal-retzius Cells ͉ Postnatal Developmentmentioning
confidence: 99%
“…In cerebral cortical development, early manipulations of the serotonergic innervation lead to altered development and plasticity in sensory areas in a variety of species (Gu and Singer, 1995;Osterheld-Haas and Hornung, 1996;Janusonis et al, 2004). In rat, neonatal systemic depletion of the cortical serotonergic innervation delays thalamocortical patterning (Blue et al, 1991) and diminishes the size of the barrel field area during the first postnatal week (Bennett-Clarke et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, several experimental paradigms and haploinsufficiency in Reln gene in mice also cause decreases in Reelin production with resultant cortical and behavioral abnormalities. 18,[39][40][41] In the heterozygous reeler mutation, there is a 50% reduction in Reelin protein and mRNA, decrease in dendritic spine density in frontal cortex, neuropil hypoplasticity, decreased GAD67 expression and decreased GABA turnover. 42 Additionally, the heterozygous reeler mutant mice exhibit decreased prepulse inhibition, 40 a phenomenon observed in schizophrenia and autism.…”
mentioning
confidence: 99%
“…45 Finally, exposure of rat pups to 5 methoxytryptamine leads to reductions in brain and blood Reelin levels, and abnormal corticogenesis. 41 Analogies between these animal models and development of schizophrenia and autism will be made and correlations will be discussed in the following passages.…”
mentioning
confidence: 99%
See 1 more Smart Citation